The best of Jay Taruc [videorecording]. ([Manila] : GMA Records, 2014)
#14 Laperal House -- Tulay -- Lapnos -- Tawid-Eskwela -- Tarima
with english subtitles.
Keywords: Documentary television programs; Documentary Videos